ADVANCED FOREIGN EXPERIENCES IN ORGANIZING PRACTICAL CLASSES FOR FUTURE SPECIALISTS BASED ON INNOVATIVE TECHNOLOGIES - Egamberdiyev Akmal Olimjanovich (Scholar Express Journals, 2023)
This article discusses the organization of practical classes of future specialists based on foreign best practices.
Keywords: innovative; scientific-professional; special